PENGARUH STRUKTUR MODAL DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SEKTOR TEKSTIL DAN GARMEN PERIODE 2010-2014 DI BURSA EFEK INDONESIA - Nurvita Sari; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The company has a long-term goal to maximize shareholder wealth. Maximizing shareholder wealth can be achieved by maximizing the present value. This study aims to determine the effect of capital structure and debt policy on the value of companies in textile and garment manufacturing enterprises in the period 2010-2014 in the Indonesia Stock Exchange partially or simultaneously. In the study population of 18 companies. And the sample in this research is as many as 8 companies. Method of determining the sample by purposive sampling method, with various criteria that have been determined. Sources of research data used are secondary data, the type of data in this study that is quantitative data. Technique of collecting data that is using method of library and method of documentation. The research used multiple linier regression analysis technique.The result of research on X1 variable is capital structure with DER & DAR indicator, while variable X2 is debt policy with DER indicator and company value with indicator of PBV. Partially variable x1 (capital structure DER & DAR) have an effect on firm value (PBV). Then on variable X2 (DER Policy)have a significant effect on firm value (PBV). While the simultaneous capital structure (DER & DAR) and Debt Policy (DER) have a significant effect on firm value (PBV).Keywords: capital structure, debt policy, corporate value